2019
DOI: 10.1016/j.ceramint.2019.02.156
|View full text |Cite
|
Sign up to set email alerts
|

Effect of tungsten based coating characteristics on microstructure and thermal conductivity of diamond/Cu composites prepared by pressueless infiltration

Abstract: Tungsten coatings were deposited on diamond particles by vacuum magnetron sputtering. The coated diamond particles were firstly heat treated at different temperatures, and diamond/copper (Cu) composites were fabricated by using a pressureless infiltration method afterwards. The influences of heat treatment on the microstructure and composition of tungsten based coating surface and diamond/copper composites were analyzed. Notable differences were found in the microstructure with heating temperatures. Moreover, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
13
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 38 publications
(13 citation statements)
references
References 37 publications
0
13
0
Order By: Relevance
“…Numerous efforts have been devoted to improving the thermal conductivity of metal matrix composites; however, there is a paucity of research literature on magnesium-based composites. The commonly used coating methods for diamond surfaces include the molten salt method, vacuum micro-evaporation, chemical vapor deposition, magnetron sputtering, and sol-gel [24,25]. The molten salt method is one of the most commonly used coating methods due to its low cost.…”
Section: Introductionmentioning
confidence: 99%
“…Numerous efforts have been devoted to improving the thermal conductivity of metal matrix composites; however, there is a paucity of research literature on magnesium-based composites. The commonly used coating methods for diamond surfaces include the molten salt method, vacuum micro-evaporation, chemical vapor deposition, magnetron sputtering, and sol-gel [24,25]. The molten salt method is one of the most commonly used coating methods due to its low cost.…”
Section: Introductionmentioning
confidence: 99%
“…Scholars found that tungsten layers can be coated on diamond by a microvacuum evaporation diffusion method and then, diamond/copper composites can be prepared by vacuum pressureless infiltration. The resulting full uniform plating layer on the diamond/copper interface has high thermal conductivity [ 16 ].…”
Section: Introductionmentioning
confidence: 99%
“…It has not only high hardness and chemical stability but also excellent thermal conductivity (600-2000 W/m•K) and thermal stability, so it is now widely used for polishing, as a particle reinforcement and as a composite coating, for example [13][14][15]. The interface bonding strength between the matrix and diamond may be primarily due to mechanical mixing without a transition layer [16]. The interface between the Fe matrix and diamond particles is the major determinant of the Fe/diamond composite properties.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…For example, diamond, which is a highly ordered crystalline solid, has the highest known thermal conductivity 2300 W (m K) -1 at room temperature. Composite materials made of diamond and copper with the thermal conductivity of 768 W (m K) -1 can be prepared by pressureless infiltration(Jia et al, 2019;Parashchuk, 2016). Despite their higher price, diamond/copper heat sinks are used in the cooling of sensitive electronic components such as power diode lasers because of the excellent thermal conductivity of diamond.…”
mentioning
confidence: 99%